PENCAK SILAT SEBAGAI SISTEM (STUDI KASUS PENCAK SILAT PANGEAN) - Ari Afrizal Sandi; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Pencak Silat is a traditional self-defense which comes from Indonesia aims to defend themselves and the group from natural challenges, they learn self-defense by following animal’s movement clay are nearby. Many people interest to join Pencak Silat Pangean, but the Pencak Silat slightly closed, so the consequently is a little bit difficult for outside people to join this Pencak Silat. This research aims to know the procedures in Pencak Silat Pangean. What factor people interest to join Pencak Silat Pangean and what positive and negative impact when joining Pencak Silat Pangean. The research metodh is use descriptive qualitative. To know the result of the study, so use observation, interview, and documentation technique. And for the subjects research is use t purposive sampling technique. The result show that a person who joining Pencak Silat Pangean is for self-defense, Pencak Silat is interpreted by self-defense’s art. There is religious element that cointained in this Pencak Silat Pangean mengajarkan who teach us for always cautious to Tuhan Yang Maha Esa.Keyword : Social System, Pencak Silat